Administrative Judicial System Evaluation from Files Alleging Medical Malpractice: Experience of Hacettepe University Faculty of Medicine, Department of Forensic Medicine - Tümer, Ali Rıza; Elden, Uğur; Çal, Sedat; Cavlak, Mehmet (The Bulletin of Legal Medicine, 2023)
Objective: For the continuity of health, health workers continue their duties uninterruptedly. In the meantime, despite all the precautions taken, some negativities may occur. Damages incurred will have to be compensated by the administration. In this study, we discussed the functioning of the administrative justice system in medical malpractice claims. Methods: In our study, 172 files sent to HUTF Forensic Medicine Department between 01.01.2019-30.04.2021 were examined. Parameters such as the date of the interim decision, the issue requested by us, the form of the expert witness request, and the result have been examined. Results: When the results of the files with the claim of medical malpractice are examined, 11 of the files (29.73%) were found to be defective, and 26 of them (70.27%) were found to be non-attributable. When the files are analyzed by years, an increase has been observed in recent years and the reason for this increase is thought to be the fast functioning of the administrative justice system and its low cost. Conclusion: Administrative justice system frequently uses forensic medicine structure. For this reason, we think that forensic medicine experts will make a positive contribution to increasing the efficiency of the system’s functioning mechanism and reducing the disruptions in practice.